Influence of Bacillus sp. on soil chemical and microbiological attributes and development of soybean and maize - Alves, Alex João; Sene, Danielly Wisoczynski de; Paula, Gabriel Ferreira de; Demétrio, Gilberto Bueno; Matsumoto, Leopoldo Sussumu (Revista Mexicana de Ciencias Agrícolas, 2021)
Plant growth-promoting rhizobacteria (PGPR) inhabit the rhizosphere of several cultivated plants. Bacteria of the genus Bacillus have great functional importance in plant development. The objective of this research was to evaluate different doses of Bacillus sp. in the development of soybean and corn crops and in the chemical and microbiological attributes of the soil. The essays were conducted in the field in the 2016/2017 harvest. The soybean and corn seeds were treated with two doses of Bacillus sp. at a concentration of 109 CFU ml-1, with 10 and 20 ml of 100 kg of seed used in soybeans and 80 and 100 ml of 100 kg of seed in corn. The experiments were completely randomized in block with four repetitions. Chemical and microbiological attributes and plant development were evaluated. The results showed that the microbial activity was achieved at the dose of 20 ml of Bacillus sp. and positively influenced the weight of the grains and soybean productivity. In corn crops, the dose of 80 ml of Bacillus sp. showed better performance on chemical and microbiological attributes, resulting in increased shoot and root mass, and a significant increase in productivity. From the results obtained, it can be concluded that the use of Bacillus sp. it is a viable alternative for sustainable agriculture, and the dose of 20 ml and 80 ml of 100 kg of soybean and corn seeds, respectively, presented better results in microbial activity and in the development of plants.